T cell exhaustion potential of bacterial superantigens relevant in severe infections and cancer - Tantoush, Fisal Alhadi Ali (2023)
Bacterial superantigens (SAgs) trigger oligoclonal activation of T cells by crosslinking MHC-class-II, on Ag-presenting cells, to the T cell receptor (TCR)/CD28, on T cells, which can be independent of Lck, a critical kinase normally involved in TCR signal. This promotes pro-inflammatory cytokine release, relevant for sepsis and cancers (e.g., chronic lymphocytic leukaemia, CLL). T cell exhaustion reduces long-term memory responses in sepsis and CLL, however whether SAgs drive this remains unclear. We hypothesized that SAgs may drive T cell exhaustion to different extents, compromising immunity in CLL patients, posing them at risk of sepsis. Mouse and human immune cells were stimulated with SAgs, including staphylococcal enterotoxins-A and B,toxic-shock syndrome toxin-1 and streptococcal pyrogenicexotoxin-K/L, compared to anti-CD3/anti-CD28 antibodies. Thereafter, T cell phenotype, function and transcription factor expression were evaluated in flow cytometry and/or next-generation sequencing. We show that bacterial SAgs differed in driving T cell exhaustion in healthy donors, CLL patients and mice. While SAgs activated naive more than memory T cells (independent of Lck), they drove Lck-dependent exhaustion. Thus, SAg exposure may worsen CLL patients dysregulated immunity and treatment outcomes. We found that ibrutinib treatment impaired-naive CD8+ T cell responses and IFNγ-secretion, while increasing exhaustion marker (TIM3) expression. SAgs-exposure further augmented T cell exhaustion phenotypes combined with defective regulatory T cell (Treg) responses. IL-7, previously reported to restore infection and cancer-specific T cell responses could not revert SAg-driven exhaustion. Finally, looking at the impact on CLL-B (cancer) cells, ibrutinib treatment decreased costimulation and memory phenotype, while SAg-exposure potentiated CLL-B cell-driven inflammation (Ag-presentation/TNFα), increasing infection/sepsis risk. In conclusion, while Lck is dispensable for T cell activation, it remains essential for SAg-driven exhaustion, which can worsen (especially ibrutinib-treated) CLL patient immunity, by promoting T cell exhaustion, CLL-B cells-induced inflammation, and lack of anti-inflammatory Tregs.